Role of mechanical erosion in controlling the effusion rate of basaltic eruptions - Antonello Piombo; Andrea Tallarico; Michele Dragoni (Geophysical Research Letters)
Abstract In many basaltic eruptions, observations show that the effusion rate of magma has a typical dependence on time: the effusion rate curves show first a period of increasing and later a decreasing phase by a maximum value. We present a model to explain this behavior by the emptying of a magma reservoir through a vertical cylindrical conduit with elliptical cross section, coupled with the its widening due to mechanical erosion, produced by the magma flow. The model can reproduce the observed dependence on time of effusion rate in basaltic eruptions. Eruption duration and the maximum value of effusion rate depend on the size of magma chamber, on lava viscosity and strongly on erosion rate per unit traction.